Ovarian Dysgerminoma – Challenging Presurgical Diagnosis and Mini-Mally Invasive Treatment - K, Otto; O, Ebertz; C, Matsingou; D, Andrikos; RL, De Wilde; H, Krentel (Archives of Clinical and Medical Case Reports, 2023)
Dysgerminoma is a rare malignant germ cell tumor of the ovary that often affects women in reproductive age. The presurgical differentiation of dysgerminoma from benign conditions is challenging. In early stages, malignant dysgerminoma can be treated with fertility sparing surgery. We present a pictorial non-systematic review of literature, discuss diagnostic challenges in ultrasound and radiological imaging and present laparoscopic treatment options in a young woman with dysgerminoma.